The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/ijms23073488
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning Analysis of Serum Proteomics in Neuropathic Pain after Nerve Injury in Breast Cancer Surgery Points at Chemokine Signaling via SIRT2 Regulation

Abstract: Background: Persistent postsurgical neuropathic pain (PPSNP) can occur after intraoperative damage to somatosensory nerves, with a prevalence of 29–57% in breast cancer surgery. Proteomics is an active research field in neuropathic pain and the first results support its utility for establishing diagnoses or finding therapy strategies. Methods: 57 women (30 non-PPSNP/27 PPSNP) who had experienced a surgeon-verified intercostobrachial nerve injury during breast cancer surgery, were examined for patterns in 74 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 115 publications
1
7
0
Order By: Relevance
“…This chemokine is expressed by the endothelium, macrophages, and Th17 lymphocytes [135]. In 2022, it was reported that in patients who developed persistent postoperative neuropathic pain (PPSNP) after breast cancer surgery, the level of CCL20 was increased [136]. Moreover, other recently published data have shown that a high level of CCL20 is strongly associated with thermal allodynia in patients after traumatic nerve injuries [137].…”
Section: Upregulation In Neuropathicmentioning
confidence: 99%
See 1 more Smart Citation
“…This chemokine is expressed by the endothelium, macrophages, and Th17 lymphocytes [135]. In 2022, it was reported that in patients who developed persistent postoperative neuropathic pain (PPSNP) after breast cancer surgery, the level of CCL20 was increased [136]. Moreover, other recently published data have shown that a high level of CCL20 is strongly associated with thermal allodynia in patients after traumatic nerve injuries [137].…”
Section: Upregulation In Neuropathicmentioning
confidence: 99%
“…CCR9 is a selective target for CCL25. The role of the CCL25/CCR9 axis in the development of neuropathy requires research; however, in 2022, it was shown that in the CSF of patients who developed postoperative neuropathic pain after breast cancer surgery, an enhanced level of CCL25 was observed [136].…”
Section: Upregulation In Neuropathicmentioning
confidence: 99%
“…Neural Networks (NN) [33], [25], [34], [26], [27], [28], [51], [52], [16], [10], [46], [38], [53], [54], [55], [56], [31] Composed of node layers, containing an input layer, one or multiple hidden layers and an output layer. Could be supervised, unsupervised or semi-supervised.…”
Section: Regressionmentioning
confidence: 99%
“…Their study highlighted that global DNA methylation held a comparable diagnostic accuracy for persistent pain, compared to established non-genetic predictors. Finaly, Lotsch et al (2022) [53] explore the potential of ML techniques such as (PCA, NN, RF) to identify proteins that distinguish patients with persistent postsurgical neuropathic pain (PPSNP). The study revealed 19 proteins that showed significant differences between the groups, marking a key finding.…”
Section: Ai/ml Models Used For Cancer Treatment Induced Pain Researchmentioning
confidence: 99%
“… 11 , 12 , 13 Taking breast cancer for example, the causes of pain include surgical outcome, tumor spread, bony metastasis to the spine, and chemotherapy. 14 , 15 It is worthy to mention that cancer-related neuropathic pain is generally associated with poor outcomes. 16 , 17 Of interest, Rayment et al have reported that cancer patients with neuropathic pain have worse physical, cognitive, and social functioning.…”
Section: Introductionmentioning
confidence: 99%